2020
DOI: 10.1177/0308518x20909391
|View full text |Cite
|
Sign up to set email alerts
|

Standards and SSOs in the contested widening and deepening of financial markets: The arrival of Green Municipal Bonds in Mexico City

Abstract: Particularly since the financial crisis of 2008, much has been written about the growing influence of finance in the development of cities in the global North. Today, financial markets also appear to be expanding southwards. A small but growing number of existing studies on the financialization of Southern cities helpfully explore how international investment changes urban development locally. Yet, they say less about the actors, procedures, and hurdles through which global market expansion is forged and expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 91 publications
0
30
0
Order By: Relevance
“…The integrity, verification and authority of standards and the efficacy of reporting and disclosure are often context specific, and require evaluation in specific case studies. Hilbrandt and Grubbauer, for example, explore the role of standards and standards‐setting organizations in fostering market expansion and financial deepening in Mexico City, and show that while standards barely impacted project implementation, they did work “as vehicles through which infrastructures of markets, knowledge, and political support were built, legitimized, and secured…[which] widened and deepened financialization” (Hilbrandt & Grubbauer, 2020, 1). Reporting and disclosure, aside from their impact on specific project quality, are technologies of neoliberal, market‐based climate change governance.…”
Section: The Governance Of Climate Financementioning
confidence: 99%
“…The integrity, verification and authority of standards and the efficacy of reporting and disclosure are often context specific, and require evaluation in specific case studies. Hilbrandt and Grubbauer, for example, explore the role of standards and standards‐setting organizations in fostering market expansion and financial deepening in Mexico City, and show that while standards barely impacted project implementation, they did work “as vehicles through which infrastructures of markets, knowledge, and political support were built, legitimized, and secured…[which] widened and deepened financialization” (Hilbrandt & Grubbauer, 2020, 1). Reporting and disclosure, aside from their impact on specific project quality, are technologies of neoliberal, market‐based climate change governance.…”
Section: The Governance Of Climate Financementioning
confidence: 99%
“…Geographers have shown that methods of evaluating 'green-ness' and creditworthiness are central to the production of risk and surplus value for green bonds (Bigger, 2017;Christophers, 2018b). They have also considered the project level impact of voluntary product standards (Hilbrandt & Grubbauer, 2020) and the relationship between certification and the realisation of financial and environmental value (Bracking, 2015). In the latter case, the question of additionality is drawn into an analysis of value that raises political concerns about fairness and deserts.…”
Section: Incomes Over Outcomesmentioning
confidence: 99%
“…This concern is best demonstrated in the work of Bracking (2015) and Hilbrandt and Grubbauer's (2020) study of standard setting organisations (SSOs). Standards are considered a pivotal piece of market infrastructure even if they cannot fully make things the same (Timmermans & Epstein, 2010).…”
Section: Incomes Over Outcomesmentioning
confidence: 99%
“…Many "regular" bonds, furthermore, have been and continue to be used to fund environmental projects, in the case of cities to create, fund and maintain parks and playgrounds, for land conservation or flooding infrastructure. With the ability to fund projects through regular bond issuances, why are increasing numbers of municipalities in particular across the Global North and increasingly the Global South (Bigger and Millington, 2020;Hilbrandt and Grubbauer, 2020) issuing green bonds? Why create this new financial product, which generates additional reporting and portfolio management work?…”
Section: Introductionmentioning
confidence: 99%